Design, Synthesis, and Application of an Optimized Monofluorinated Aliphatic Label for Peptide Studies by Solid‐State 19F NMR Spectroscopy. (5th October 2016) - Kokhan, Serhii O.; Tymtsunik, Andriy V.; Grage, Stephan L.; Afonin, Sergii; Babii, Oleg; Berditsch, Marina; Strizhak, Alexander V.; Bandak, Dmytro; Platonov, Maxim O.; Komarov, Igor V.; Ulrich, Anne S.; Mykhailiuk, Pavel K.
Abstract: A conformationally restricted monofluorinated α‐amino acid, (3‐fluorobicyclo[1.1.1]pentyl)glycine (F‐Bpg), was designed as a label for the structural analysis of membrane‐bound peptides by solid‐state 19 F NMR spectroscopy. The compound was synthesized and validated as a 19 F label for replacing natural aliphatic α‐amino acids. Calculations suggested that F‐Bpg is similar to Leu/Ile in terms of size and lipophilicity. The 19 F NMR label was incorporated into the membrane‐active antimicrobial peptide PGLa and provided information on the structure of the peptide in a lipid bilayer.